2002
DOI: 10.1007/s007010200020
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results support the opinion, which claims the existence of underdevelopment of the occipital bone and posterior fossa in patients with Chiari type I malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…Like our outcomes, many authors reported that the length of the clivus was statistically significantly lower in the patients who developed herniation (3,4,20,21,27,29,31).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Like our outcomes, many authors reported that the length of the clivus was statistically significantly lower in the patients who developed herniation (3,4,20,21,27,29,31).…”
Section: Discussionsupporting
confidence: 74%
“…This length was found to be smaller in CMI patients in the literature, with researchers reporting that the difference was statistically significant (4,8,20,26,29,30). In this study, we found that the length of the supraocciput was 37.22 ± 4.17 mm in the CMI patients and 40.29 ± 4.79 mm in the controls.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations